Integrated MED and HDH desalination systems for an energy-efficient zero liquid discharge (ZLD) system - Furqan Tahir (14429547) (2022)
The Persian Gulf hosts densely located desalination plants that represent 50% of the global seawater desalination. The salinity levels in this gulf, especially in Qatar, are very high because of constant brine discharge and the shallow seawater ( ∼ 35 m depth). With the growing population, more desalination plants need to be installed to meet freshwater demands. The rising salinity levels and the ambient and sweater temperature will raise the specific energy consumption to produce a unit distillate because of climate change. Furthermore, the brine discharge affects the marine ecosystem and deteriorates the soil and groundwater quality. Thus, it is imperative to design and innovate a low or zero liquid discharge (LLD or ZLD) desalination system to mitigate climate change impacts and guarantee a safe marine environment. One such ZLD system is proposed and assessed in this study. The multi-effect desalination (MED) with higher top brine temperature (75 °C) is integrated with humidification dehumidification (HDH) system for brine concentration. In the final stage, the salts are removed via an evaporative crystallizer using thermal energy. The performance ratio (PR) with top brine temperature and temperature difference across each evaporator is evaluated and discussed. Finally, the specific energy consumption of the ZLD system is analyzed for different operating conditions. Other Information Published in: Energy Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.egyr.2022.01.028